Sarcopenia is associated with mortality in non-critical elderly patients visiting the emergency department - Liao, Mei-Chen; Yen, Cheng-Chang; Lin, Yuh-Te; Huang, Fong-Dee; Chang, Yun-Te (Frontiers in Medicine, 2023)
Introduction Geriatric syndrome (GS) increases risk of disability and mortality in older adults. Sarcopenia is a predominant illness of GS and accelerate its progression. This study aimed to investigate associations between mortality, emergency department (ED) re-visits and GS-related illnesses among older adults who visited the ED. Method This retrospective observational study enrolled elderly patients who visited the ED in our hospital between January 2018 and October 2020. Patients were evaluated for potential sarcopenia, which was defined by both low handgrip strength and calf circumference. Follow-up was at least 6 months. Data of age, gender, mortality, ED re-visits, and GS-related illnesses were collected and analyzed for associations. Results A total of 273 older adults aged 74 years or older were included, of whom 194 were diagnosed with possible sarcopenia. Older adults with possible sarcopenia also had significantly lower body mass index (BMI); a higher proportion needed assistance with daily activities; more had malnutrition, frailty, and history of falls (all p < 0.001) and acute decline in activities of daily living (p = 0.027). Multivariate analysis showed that possible sarcopenia [adjusted hazard ratio, aHR): 9.89, 95% confidence interval (CI): 1.17–83.81, p = 0.036], living in residential institutions (aHR: 2.85, 95% CI: 1.08–7.50, p = 0.034), and frailty (aHR: 7.30, 95% CI: 1.20–44.62, p = 0.031) were associated with mortality. Aged over 85 years (adjusted odds ratio: 2.44, 95% CI: 1.25–4.80, p = 0.02) was associated with ED re-visits. Conclusion Sarcopenia is associated with mortality among older adults who visit ED. Initial screening for sarcopenia and relevant risk factors among older adults in the ED may help with early intervention for those at high-risk and may improve their prognosis.